Global economic elites and the new spirit of capitalism: careers and collective mindsets of economic elites compared - Pohlmann, Markus; Elias, Friederike (Organization, Management and Crime - Organisation, Management und Kriminalität, 2024)
Economic Neoliberalism -- Research Perspective -- The Operationalization of the study -- Collective Mindsets -- Germany -- Established Global Elites with Neoliberal Mindsets -- Neoliberal State Capitalism in China -- Modern Family Capitalism in South Korea -- Japan's Flashback to Traditional Capitalism -- All at the Same Time -- Restructuring Modernity -- Traditional Modernity -- Global and Bankrupt.